2005
DOI: 10.1194/jlr.m500024-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the barrier: net flux of 27-hydroxycholesterol into the human brain

Abstract: Side chain oxidized oxysterols have a unique ability to traverse lipophilic membranes. We tested the hypothesis that there is a net flux of 27-hydroxycholesterol from the circulation into the brain using plasma samples collected from the internal jugular vein and an artery of healthy male volunteers. Two independent studies were performed, one in which total levels of 27-hydroxycholesterol were measured and one in which the free fraction of 27-hydroxycholesterol was measured. In the majority of subjects studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
238
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(252 citation statements)
references
References 27 publications
12
238
0
2
Order By: Relevance
“…One possibility is that cholesterol metabolites that can cross the blood brain barrier, particularly 27-hydroxcholesterol, may have had some influence on learning (Heverin et al, 2005). There is some evidence, albeit indirect, for the involvement of 27-hydroxycholesterol in learning and memory because levels of this oxysterol are significantly reduced in patients with mild cognitive impairment, Alzheimer's disease and vascular dementia (Kolsch et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that cholesterol metabolites that can cross the blood brain barrier, particularly 27-hydroxcholesterol, may have had some influence on learning (Heverin et al, 2005). There is some evidence, albeit indirect, for the involvement of 27-hydroxycholesterol in learning and memory because levels of this oxysterol are significantly reduced in patients with mild cognitive impairment, Alzheimer's disease and vascular dementia (Kolsch et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, normal levels of this oxysterol are relatively very low in the hippocampus in comparison to 24S--OHC. We have previously shown that a substantial part of this cerebral 27--OHC originates from outside the brain ( Heverin et al, 2005). While we have evidence to suggest that it further metabolized to an acid which then fluxes out of the brain we do not know the function of 27--OHC in the brain ( Meaney et al, 2007).…”
Section: Introductionmentioning
confidence: 86%
“…The data indicate that LXR ligands are efficiently deactivated in brain before passage into CSF. This is true whether the ligands are supplied via the bloodstream (21) or produced in brain (22,24).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of 7␣-hydroxy-3-oxocholest-4-en-26-oic and 3␤-hydroxycholest-5-en-26-oic acid in CSF were found to be 7.170 Ϯ 2.826 and 0.416 Ϯ 0.193 ng/ml, respectively. These C 27 bile acids could originate in plasma and be transferred to CSF or alternatively be formed in brain from 27-hydroxycholesterol (22,24), which is itself suggested to be imported into brain from plasma (21). The possibility also exists that C 27 bile acids could be formed in brain from cholesterol itself.…”
Section: Identification Of Sterols and Bile Acids In Csfmentioning
confidence: 99%
See 1 more Smart Citation